Pengaruh Penggunaan Structured Dyadic Methods Terhadap Pemahaman Konsep Matematika Siswa di Sekolah Menengah Pertama Negeri 5 Kota Jambi - Sunarto Sunarto (Jurnal Kajian Penelitian Pendidikan dan Kebudayaan, 2024)
This research was conducted to seek evidence, answer questions and determine the clarity and certainty of how much influence the results of the application of Structured Dyadic Methods have on Mathematical Concepts Understanding of Students in Junior High School 5 in Jambi City. This study is a quantitative research methods, namely posttest only control design. the sample was taken by using the simple random sampling techniques. While the data was collected using the mathematics concept comprehension test instruments. The research sample consisted of 20 students as an experimental class using the Structured Dyadic Methods, and a total of 20 students as a control class using Direct Instruction Method. From the data described, it was found that the maen value of the experimental group is and a standard deviation of , while the mean of the control group was and the standard deviation was 9,74. The results of the calculation of the t test value of the t test with a significant level of 5% while 1% and obtained . Because the value of is . While the correlation is obtained 0,55 and after comparing between it turns out (Both at the 5% and 1% significance levels) The alternative hypothesis is acceptedwhich means that there is a difference between the Structured Dyadic Methods Matchin the ability to understand mathematical concepts of students at Junior Hight School students 5 Jambi City.